Stone Fox y la carrera de trineos - Gardiner, John Reynolds; Sewall, Marcia; Gardiner, John Reynolds (Barcelona : Noguer y Caralt, 1996)
Little Willie hopes to pay the back taxes on his grandfather's farm with the purse from a dog sled race he enters.
Translation of: Stone Fox.
"A partir de 10 años"--Back cover.
Accelerated Reader
Keywords: Sled dog racing -- Juvenile fiction; Carreras de trineo -- Novela juvenil